Gains from Trade in Tax Revenue and the Efficiency Case for Trade Taxes - Jeremy Edwards (Center for Economic Studies and ifo Institute (CESifo), 2003)
The paper analyses the gains from trade in distortionary tax revenue between countries, focussing on the case where lump-sum reveue transfers are restricted. In this case, trade taxes can be used to transfer government revenue between countries, and such taxes will typically be used in Pareto-efficient international equilibria. Global production efficiency conditions are often, though not always, satisfied at Pareto-efficient allocations involving trade taxes, but the implications for international taxation differ from those that have been put forward on the basis of the Diamond-mirrlees production efficiency theorem.
Keywords: 330